Improving Student’s Scientific Literacy Skill Through POGIL with Socioscientific Issues Context on the Topic Enviromental Pollution - Anggi, Oktari Pradina; Hernani, Hernani; Solihat, Rini (Proceedings of International Conference on Biology and Applied Science, 2019)
Abstract. Scientific literacy skill is one of the 21 st century important skills needed to be developed in science learning. The purpose of this study is to inform students ability in scientific competence aspect of scientific literacy through Process Oriented Guided Inquiry Learning (POGIL) model with Socioscientific Issues (SSI) context on environmental pollution topic. The population in this research was all grade VII students of one of junior high school in Bandung and 53 students as research sample. The research used quasi-experimental design with 24 multiple choice questions items as research instrument. The experimental class was teached through POGIL with SSI context, while the control class was teached through scientific approach. Result obtained from t-test on normal and homogenous data shows that there are significant difference. N-gain of the indicators: explaining phenomena scientifically in the experiment class is 0.46 while in the control class is 0.17, evaluate and design scientific enquiry in the experiment class is 0.5 while in the control class is 0.25, interpret data and evidence scientifically in the experiment class is 0.75 while in control class is 0.71. Sientific literacy between students who received POGIL with SSI context is better than students who received scientific approach.